Online reduced gaussian process regression based generalized likelihood ratio test for fault detection. (January 2020) - R., Fezai; M., Mansouri; K., Abodayeh; H., Nounou; M., Nounou
Highlights: A generalized likelihood ratio test (GLRT) based online reduced GPR, named ORGPR-based GLRT, is developed. ORGPR-based GLRT fault detection approach is proposed to enhance chemical process monitoring. The detection performance of the new chart is studied using Tennessee Eastman process (TEP). The detection results are evaluated using three fault detection criteria: the missed detection rate (MDR), the false alarm rate (FAR) and the computation time (CT). Abstract: In this paper we consider a new fault detection approach that merges the benefits of Gaussian process regression (GPR) with a generalized likelihood ratio test (GLRT). The GPR is one of the most well-known machine learning techniques. It is simpler and generally more robust than other methods. To deal with both high computational costs for large data sets and time-varying dynamics of industrial processes, we consider a reduced and online version of the GPR method. The online reduced GPR (ORGPR) aims to select a reduced set of kernel functions to build the GPR model and apply it for online fault detection based on GLRT chart. Compared with the conventional GPR technique, the proposed ORGPR method has the advantages of improving the computational efficiency by decreasing the dimension of the kernel matrix. The developed ORGPR-based GLRT (ORGPR-based GLRT) could improve the fault detection efficiency since it is able to track the time-varying characteristics of the processes. The fault detection performance of the developed ORGPR-based GLRT method is evaluated using a Tennessee Eastman process. The simulation results show that the proposed method outperforms the conventional GPR-based GLRT technique.